Sufficient Optimality Conditions for a Bilevel Semivectorial D.C. Problem. (18th November 2018) - Gadhi, Nazih Abderrazzak; Dempe, Stephan
Abstract: The paper is devoted to the study of a bilevel multiobjective optimization problems with objectives and constraints given as differences of convex functions. The main attention is paid to deriving sufficient optimality conditions. Several intermediate optimization problems are introduced to help us in our investigation.